Is there an association between body image and self-rated oral health in a sample of Brazilian adolescents? - Auristhela Martinez ACEVEDO; Ana Leticia Andries e ARANTES; Lilian Maria de Moraes ANDRADE; Eliane Rodrigues de FARIA; Michele Pereira NETTO; Renata Maria Souza OLIVEIRA; Ana Paula Carlos CÂNDIDO; Isabel Cristina Gonçalves LEITE (Brazilian Oral Research)
Abstract The aim of this study was to evaluate the association of body image perception and self-assessment of oral health with other associated factors in a sample of Brazilian adolescents. This cross-sectional study involved a total of 281 adolescents aged 14 to 19 years enrolled in 29 public schools from May 2021 to December 2023 in the urban area of Juiz de Fora, state of Minas Gerais, Brazil. The total enrollment of 9,502 participants in the first stage of the study () was considered for sample size calculation. The prevalence of negative self-assessment of oral health in the adolescent population was estimated at 18%, with a standard error of 1%, a 95% confidence interval, and a 20% loss to follow-up. Participants completed a questionnaire via the Google Forms platform, which gathered information on their socioeconomic status, self-perception of body image, self-assessment of oral health, and self-esteem. Bivariate analysis and logistic regression models were used to evaluate the associations between variables. Variables with p < 0.10 in the bivariate analysis were included in the logistic regression model. Variables with p < 0.05 were retained in the final model. The final logistic regression model revealed that adolescents with a higher socioeconomic status rated their oral health as excellent or good. Additionally, those who reported not living with their parents and had a low level of self-esteem had a poor oral health self-assessment. Adolescents’ perception of their body image was not associated with oral health self-assessment. On the other hand, socioeconomic factors, family structure, and self-esteem influenced adolescents’ oral health self-assessment.